2015
DOI: 10.1016/j.yjmcc.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor regulates cardiac function and tissue remodeling in a mouse model of dilated cardiomyopathy

Abstract: Cardiac structural changes associated with dilated cardiomyopathy (DCM) include cardiomyocyte hypertrophy and myocardial fibrosis. Connective Tissue Growth Factor (CTGF) has been associated with tissue remodeling and is highly expressed in failing hearts. Our aim was to test if inhibition of CTGF would alter the course of cardiac remodeling and preserve cardiac function in the protein kinase Cε (PKCε) mouse model of DCM. Transgenic mice expressing constitutively active PKCε in cardiomyocytes develop cardiac dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 40 publications
3
21
0
1
Order By: Relevance
“…Masson trichrome staining showed evidence of interstitial myocardial fibrosis in TmcsMed1 -/- heart (Fig 6A and 6B). Previous studies have shown that interstitial myocardial fibrosis is associated with increased expression of TGFβ2, CTGF and collagenase 9a2 [52,53]. In agreement with this, the TmcsMed1 -/- heart showed elevated expression of the above three genes (Fig 6C, 6D and 6E).…”
Section: Resultssupporting
confidence: 86%
“…Masson trichrome staining showed evidence of interstitial myocardial fibrosis in TmcsMed1 -/- heart (Fig 6A and 6B). Previous studies have shown that interstitial myocardial fibrosis is associated with increased expression of TGFβ2, CTGF and collagenase 9a2 [52,53]. In agreement with this, the TmcsMed1 -/- heart showed elevated expression of the above three genes (Fig 6C, 6D and 6E).…”
Section: Resultssupporting
confidence: 86%
“…Data from previous studies have found tissue CTGF expression is upregulated in people with fibrotic diseases, including cirrhosis , cardiac fibrosis , crescentic glomerulonephritis , idiopathic pulmonary fibrosis , and systemic sclerosis . In addition, pharmacological blockade or genetic deletion of CTGF ameliorates the progression of fibrosis in various mouse organs . Together, these findings support the concept that adipose tissue fibrosis is involved in the pathogenesis of insulin resistance associated with obesity in humans, which has previously been demonstrated in rodent models .…”
Section: Discussionsupporting
confidence: 83%
“…Recently, the profibrogenic cytokine connective tissue growth factor (CTGF, CCN2), a cysteine-rich matricellular protein of the CCN family, has been implicated in mediating a variety of cellular processes, including adhesion, proliferation, differentiation, migration, angiogenesis and extracellular matrix (ECM) production, all of which are common features of tissue remodelling and fibrosis 10 11. Evidence has been introduced and suggested that overexpression of CTGF has been noted in numerous fibrotic disorders, including pulmonary,12 renal,13 hepatic,14 skin15 and cardiac fibrosis 11 16.…”
mentioning
confidence: 99%